Development of Performance Grading Map of Nepal Based on Superpave System - Kharbuja, Sunita; Shahi, Thusitha Chandani; Duwal, Rajan (Journal of Science and Engineering, 2020)
The Performance of the bituminous binder plays important role in the overall performance of the pavement system. One of the major cause of pavement failure is the bitumen grade, i.e selection of suitable grade of bitumen. Therefore, performance grading of bituminous binder is inevitable for the specific temperature and climatic zones. This study is focused on the determination of performance grading of bituminous binder for various temperature zones in Nepal. In this study, twenty one years’ daily maximum and minimum secondary temperature data of 70 meteorological stations were collected and were analyzed for temperature zoning. Performance grading of bituminous binder was conducted with the help of Strategic Highway Research Program (SHRP) and Long-Term Pavement Performance Program (LTPP) prediction models. The concept of Superpave has been adopted for the analysis, which stands for superior performing asphalt pavement. The Superpave mix design includes a new analysis system based on performance characteristics of the pavement layer. The bituminous binder grades for Nepal have been determined on the basis of air temperature thereafter predicting the pavement temperatures. The study has determined seven different performance grade zones based on SHRP and four different performance grade zones based on LTPP model. The study synthesized the Performance Grade (PG) map of the country.